UPAYA MENINGKATKAN MOTIVASI BELAJARPADA PEMBELAJARAN LOMPAT TINGGI GAYA STRADDLESISWA KELAS VIII C SMPN 4 DEPOK TAHUN AJARAN 2009/2010DENGAN METODE MENGAJAR INKLUSI - Muhammad Arief Wibowo dan Bangkit Seandi Taroreh (Pelita - Jurnal Penelitian Mahasiswa UNY, 2009)
This research is aimed to increase the students’ extrinsic and intrinsic learningmotivation on the high jump material of straddle style using the inclusion teachingmethod. The use of this method involves some tasks adapted to the students’ ability.This research is a classroom action research. The subject of the research was thestudents Grade VIII C at SMP N 4 Depok, Sleman, Yogyakarta. Cycle 1 was done in twomeetings, involving planning, implementation actions, reflection and observation. Thetechnique of collecting the data was observation and interview. The data were analyzedby using descriptive analysis and reported in the form of table and diagram.The result of the research shows that the students’ intrinsic and extrinsic learningmotivation increased. It can be seen through the observation of the early condition andCycle I. The intrinsic motivation covers the interest aspect, relevance aspect, confidenceaspect, and satisfaction aspect. The interest aspect increased from 41.43% (rather good)to 68.57% (good). The aspect of relevance increased from 77.43% (good) to 100% (verygood). The aspect of confidence increased from 77.14% (good) to 81.43% (good). Theaspect of satisfaction increased form 45.71% (not good) to 80% (good). Meanwhile, theextrinsic motivation covering material aspect, environmental aspect, infrastructureaspect, and teacher aspect increased. The material aspect increased from 30.29% (verypoor) to 57.14% (rather good). The environmental aspect increased from 65.71% (prettygood) to 93.33% (very good). The infrastructure aspect increased from 78.57% (good) to81.43% (good) while the teacher aspect increased from 75.71% (good) to 78.57% (good).Keywords: Learning motivation, Inclusion teaching methods, High jump of straddle style